Relevance of Social Responsibility in the Pandemic Era − An Indian Perspective - George Abraham Kurian (Business Ethics and Leadership)
As the world’s largest democracy and the second most populated country globally, India has had a relatively severe adverse impact of the pandemic than most other countries. This research paper highlights key pandemic implications on India’s socially responsible initiatives and how these affect citizens. This once-in-a-century global health disaster turned out to be a sustainable development crisis for most nations. Due to pandemic ramifications, the worldwide progress on Sustainable Development Goals (SDGs) adopted in 2015 in its current form, has recorded reversal in several critical indices, despite the limitations of underestimating due to lack of latest or reliable data. While the pandemic has posed serious challenges to attaining country-specific SDGs, it also provided opportunities to demonstrate socially responsible behavior amidst the crisis. This paper deliberates on the individual roles and the interplay between four pillars of socially responsible behavior, meaning the government, corporate sector, social sector, and the civil society at large comprising of individuals, groups, and communities operating outside of the government and for-profit and NGO entities. The study delves in depth into key SDGs that suffered setbacks due to disruptions and health emergencies that assumed higher priority. The authorities were compelled to change course from plans. The priorities planned through Government policies had to be modified on an urgent basis, as government was also taken unawares and had to safeguard the lives and livelihood of the population. Benchmarking of SDGs was done at a country and state level. It reflects the gaps in what was attained at the highest and lowest level by various states and union territories and likely areas of improvement.